Arriving at the Right Platform for E-Learning - Kaisinath, Gurumurthy (Voices of Teachers and Teacher Educators, 2020)
Schools and educational institutions have tended to use proprietary software applications: software that is not sold, but ‘licensed’, by the vendor. Here, the institution is only a ‘user’, and neither owns the software nor has any control over it. Over the last decade, however, the Indian public school and higher education systems have made significant strides in using free and open source software (FOSS). Kerala pioneered the adoption of FOSS in schools in 2002 and many states have followed suit. This shift acquired further momentum after the National ICT Policy, 2012 of NCERT, recommended FOSS in schools. In the current COVID-19 pandemic context, e-learning has become the default method at many educational institutions. And with blended and Online learning set to become the new normal, we need to carefully weigh the relative merits of proprietary and FOSS e-learning platforms.